Complementary and Alternative Medicine : Bodies, Therapies, Senses. - Barcan, Ruth (Bloomsbury Publishing, 2013)
Alternative therapies, once the province of the hippie counterculture, are now a mainstream phenomenon. But they are more than a medical and economic sensation. At once spiritual and bodily, medical and recreational, they are an enormously popular cultural practice bound up with the pleasure-seeking drive of consumer culture as well as with spiritual and neo-liberal values. Complementary and Alternative Medicine critically examines this phenomenon - which some denounce as the triumph of superstition over reason - by asking practitioners themselves what makes these therapies so appealing. Dra.